Microplastics contamination in popular soft drinks and non-alcoholic beverages marketed in Iran: Quantity and characteristics - Edris Hoseinzadeh; Hooshyar Hossini; Pouran Makhdoumi; Parisa taha; Sheida Parsa; Tooraj Massahi (Results in Engineering)
Given the increasing reliance on plastic packaging in the beverage industry, this study investigates the presence of microplastics (MPs) in the most popular beverage brands in the Iranian market. A total of 19 bottled beverage brands, including soft drinks and non-alcoholic beverages, were randomly collected and filtered. Quantitative analysis of the MPs was then performed using stereomicroscopy and fluorescence techniques, and classification was based on color, shape, and size. In addition, the polymer type was determined using Fourier transform infrared spectroscopy (FT-IR), and the surface morphology and elemental composition of the MPs were examined using Scanning Electron Microscopy (SEM) and Energy dispersive X-ray spectroscopy (EDS). The results showed that approximately 80–90 % of the samples were contaminated with different MP types, with an average of 4.5 ± 4.8 particles/L detected by stereomicroscopy and 21.90 ± 25.72 particles/L by fluorescence microscopy. FT-IR analysis identified polyethylene terephthalate (PET) and polyethylene (PE) as the predominant polymer types and may clarify the possible role of packaging materials in the contamination of MPs. Fragments accounted for the highest proportion of MPs (71 %), followed by fibers (29 %). The size distribution of MPs was dominated by particles in the range of 1–500 μm (48 %), followed by 500–1000 μm (40 %) and 1000–1500 μm (12 %). MPs were black (84 %), with smaller proportions of red (7 %) and green (1 %), which may reflect the source of the contamination. The findings emphasize the necessity of increased monitoring and the application of countermeasures to lessen MPs contamination in the beverage sector.